French vocabulary in Encore Tricolore: do pupils have a chance? - Cornelia Tschichold (The Language Learning Journal, 2012)
British learners acquire very little vocabulary in their foreign languages,compared to pupils elsewhere in Europe, particularly learners of English as aforeign language. Could the materials used for teaching help explain thisdifference? An analysis of the vocabulary loading of a textbook for French as aforeign language commonly used in Britain, Encore Tricolore (Mascie-Taylor andHonnor, 2001, Cheltenham, UK, Nelson Thornes), was carried out with thisquestion in mind. An analysis of the vocabulary suggests that it is not introducedand practised in a way that is conducive to building a sufficiently large vocabularyto reach level B1 of the Common European Framework of Reference forLanguages (CEFR).